MERPATI DALAM KARYA GRAFIS - Yosi Selvia, Drs. Yusron Wikarya, M.Pd. Yofita sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2017)
Pigeon is a pet that has a uniqueness and beauty of shape, color, nature and activities, faithful to her lover. Characterishes Pigeons used as inspiration in creating works of art in the field of graphic relief print. Method for creating this finals worksof art using the five phases of preparation, elaboration, synthesis, andrealization of the concept began sketching move sketch, preparation of tools and materials, working and finishing processes. The last stage is the completion of up to exhibit. Title of the work in accordance with the theme of which: 1) happiness,2) Waiting Attendance, 3) Successor Generation, 4) Remember back home 5) Protect, 6) Looking for Directions, 7) Alone, 8) Responsibility, 9) Romantic, 10) Life Survivor. Each work that has been created content the same theme.Key Word: Merpati, Graphic, Relief Print.